A method for atomic-level noncontact thermometry with electron energy distribution. (17th March 2017) - Kinoshita, Ikuo; Tsukada, Chiharu; Ouchi, Kohei; Kobayashi, Eiichi; Ishii, Juntaro
Abstract: We devised a new method of determining the temperatures of materials with their electron-energy distributions. The Fermi–Dirac distribution convoluted with a linear combination of Gaussian and Lorentzian distributions was fitted to the photoelectron spectrum measured for the Au(110) single-crystal surface at liquid N2 -cooled temperature. The fitting successfully determined the surface-local thermodynamic temperature and the energy resolution simultaneously from the photoelectron spectrum, without any preliminary results of other measurements. The determined thermodynamic temperature was 99 ± 2.1 K, which was in good agreement with the reference temperature of 98.5 ± 0.5 K measured using a silicon diode sensor attached to the sample holder.